2017
DOI: 10.1002/pbc.26624
|View full text |Cite
|
Sign up to set email alerts
|

Early presentation of osteonecrosis in acute lymphoblastic leukemia: Two children from the Nordic and Baltic cohort

Abstract: Osteonecrosis (ON) is usually considered treatment related in patients with acute lymphoblastic leukemia (ALL). We report two patients with presentation of ON at the time of ALL diagnosis. Both were females and diagnosed with ALL at age 8 and 14 years. In the latter, some symptoms and radiologically verified ON in both knees were still present after the end of ALL therapy. No pediatric patients have previously been reported with ON presenting before initiation of ALL therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Further, two patients with ON were excluded from the study as they had ON diagnosed before ALL diagnosis, giving in total an ALL cohort of 1,489 patients. Overall, we confirmed symptomatic ON in 67 patients additional patients with ON were identified; ON manifested in two of the 72 patients before ALL diagnosis and they were excluded (described in previous publication 24 ). Further, three patients were moved to the non-ON group of patients-one had been incorrectly registered, one had asymptomatic ON, and one had ON after hematopoietic stem cell transplantation (SCT) ( Figure 1).…”
Section: On Registration and Classificationsupporting
confidence: 73%
See 1 more Smart Citation
“…Further, two patients with ON were excluded from the study as they had ON diagnosed before ALL diagnosis, giving in total an ALL cohort of 1,489 patients. Overall, we confirmed symptomatic ON in 67 patients additional patients with ON were identified; ON manifested in two of the 72 patients before ALL diagnosis and they were excluded (described in previous publication 24 ). Further, three patients were moved to the non-ON group of patients-one had been incorrectly registered, one had asymptomatic ON, and one had ON after hematopoietic stem cell transplantation (SCT) ( Figure 1).…”
Section: On Registration and Classificationsupporting
confidence: 73%
“…At the end of follow‐up (August 27, 2015), 67 patients were registered with ON, and through contacts with treatment centers five additional patients with ON were identified; ON manifested in two of the 72 patients before ALL diagnosis and they were excluded (described in previous publication). Further, three patients were moved to the non‐ON group of patients—one had been incorrectly registered, one had asymptomatic ON, and one had ON after hematopoietic stem cell transplantation (SCT) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, MRI at the time of ALL diagnosis has demonstrated significantly abnormal fatty marrow signal patterns in the femoral epiphyses and apophyses, 40,41 and these bone marrow infiltrations can be severe enough to induce vascular compression and an ischemic state. 42 The OPAL trial and other case report studies reported radiologically confirmed osteonecrosis at the diagnosis of ALL; these findings were not always consistently predictive of osteonecrosis during therapy, [42][43][44] but due to the small number of patients and the early follow-up MRIs performed within 6 months from diagnosis, some cases may not have been captured. Results of the ongoing British OsteoNEcrosis Study (BONES), 45 which obtains periodic MRIs in children with ALL, may shed further light on this interesting issue.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Nevertheless, both osteoporotic vertebral fractures and osteonecrosis can also manifest already at ALL diagnosis. 2,8 Although skeletal complications are well known, their management remains unestablished. Treatment optimisation is warranted as skeletal problems can significantly impair the quality of life of the survivors.…”
Section: Introductionmentioning
confidence: 99%
“…BMD deficits in paediatric cancer patients have multifactorial causes but specific risk factors are acknowledged, including corticosteroid treatment and haematopoietic stem cell transplantation (HSCT) 2,7 . Nevertheless, both osteoporotic vertebral fractures and osteonecrosis can also manifest already at ALL diagnosis 2,8 . Although skeletal complications are well known, their management remains unestablished.…”
Section: Introductionmentioning
confidence: 99%